Pengaruh Corporate Social Responsibility Dan Good Corporate Governance Terhadap Manajemen Laba - Ami Ami; Lindawati Lindawati (CV. Ulil Albab Corp, 2024)
This study aims to determine the effect of motivation and work discipline on the performance of employees at the Department of Population and Civil Registration of Tangerang City in providing administrative services. This research employs a descriptive quantitative statistical approach, using primary data. Data collection was carried out through questionnaires, with 93 respondents selected through random sampling, and data was processed using SPSS version 26. The results of the study indicate the regression equation Y = 2.423 + 0.382X1 + 0.628X2, showing that both motivation and work discipline have a positive and significant effect on employee performance. Simultaneously, motivation and work discipline positively and significantly influence employee performance, with an R square value in the determination test of 0.652. Thus, motivation and work discipline account for 65.2% of the variation in employee performance at the Department of Population and Civil Registration of Tangerang City, which is categorized as strong.